2013
DOI: 10.1016/j.yhbeh.2013.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent role of the amygdala in the development of emotional and neuroendocrine reactivity to threatening stimuli in infant and juvenile rhesus monkeys

Abstract: Amygdala dysfunction and abnormal fear and stress reactivity are common features of several developmental neuropsychiatric disorders. Yet, little is known about the exact role the amygdala plays in the development of threat detection and emotional modulation. The current study examined the effects of neonatal amygdala lesions on defensive, emotional, and neuroendocrine reactivity of infant rhesus monkeys reared with their mothers in large species-typical social groups. Monkeys received either bilateral MRI-gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 71 publications
(122 reference statements)
6
64
0
1
Order By: Relevance
“…The HI task is designed to assess emotional reactivity to a social stressor (Kalin, 1993), and the modulation of emotional behavior to different levels of social threat based on the gaze direction of an unfamiliar human [reviewed in (Coleman & Pierre, 2014)]. In addition, the HI task has been shown to rapidly activate the HPA axis and stimulate the release of glucocorticoids (Jahn et al, 2010; Kalin, Larson, Shelton, & Davidson, 1998; Kalin, Shelton, Davidson, & Kelley, 2001; Raper et al, 2013a; Raper et al, 2013b). As such, the HI task enables the measurement of both behavioral and physiological reactivity to emotionally charged stimuli.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HI task is designed to assess emotional reactivity to a social stressor (Kalin, 1993), and the modulation of emotional behavior to different levels of social threat based on the gaze direction of an unfamiliar human [reviewed in (Coleman & Pierre, 2014)]. In addition, the HI task has been shown to rapidly activate the HPA axis and stimulate the release of glucocorticoids (Jahn et al, 2010; Kalin, Larson, Shelton, & Davidson, 1998; Kalin, Shelton, Davidson, & Kelley, 2001; Raper et al, 2013a; Raper et al, 2013b). As such, the HI task enables the measurement of both behavioral and physiological reactivity to emotionally charged stimuli.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the intruder left the room leaving the animal alone for another 10 minutes (Alone 2). A different rubber masks was worn by the intruder at each age of testing, so that the same intruder was seen at each age across all subjects in our laboratory (Raper et al, 2013a; Raper et al, 2013b; Raper et al, 2017). The intruder wore a rubber mask to provide a uniform stimulus to each subject.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, in a study by another lab, amygdala lesions in young adult monkeys reduced the duration of freezing and reduced cortisol levels in response to a new environment (Machado and Bachevalier, 2008). In contrast to behavioral effects of adult lesions, recent studies have shown that neonatal amygdala lesions in monkeys result in increased freezing during threat (NEC condition; Raper et al, 2013b, 2013c). Typically, monkeys display a modulation of fearful, hostile, and defensive behavior across the human intruder paradigm; however, monkeys with neonatal amygdala lesions displayed similar levels of fearful, hostile, and defensive behavior across the conditions (ALN, NEC, and ST) of the human intruder paradigm at two to four months of age (Raper et al, 2013b, 2013c).…”
Section: Neural Basis Of Inhibited Temperamentmentioning
confidence: 98%
“…In contrast to behavioral effects of adult lesions, recent studies have shown that neonatal amygdala lesions in monkeys result in increased freezing during threat (NEC condition; Raper et al, 2013b, 2013c). Typically, monkeys display a modulation of fearful, hostile, and defensive behavior across the human intruder paradigm; however, monkeys with neonatal amygdala lesions displayed similar levels of fearful, hostile, and defensive behavior across the conditions (ALN, NEC, and ST) of the human intruder paradigm at two to four months of age (Raper et al, 2013b, 2013c). Neonatal amygdala lesions also resulted in a flattened diurnal cortisol rhythm in monkeys at 5 months of age (Raper et al, 2013a) and blunted cortisol response to stress in young adult monkeys (Raper et al, 2013c).…”
Section: Neural Basis Of Inhibited Temperamentmentioning
confidence: 98%
See 1 more Smart Citation